Three German invasions of France : the summer campaigns of 1870, 1914 and 1940 - Fermer, Douglas (Pen & Sword Military, 2013)
Tension and rivalry between France and Germany shaped the history of Western Europe in the century from 1860. Three times that hostility led to war and the invasion of France - in 1870, 1914 and 1940. The outcomes of the battles that followed reset the balance of power across the continent. Yet the German invasions tend to be viewed as separate events, in isolation, rather than as connected episodes in the confrontation between the two nations.